A systematic review of adapting immersive technology in enhancing teaching and learning for students in higher education - Jantan, Azrul Hazri; Abdullah, Lili Nurliyana; Roslan, Nuur Alifah; Khamis, Nor Huzani; Khairudin, Moh. Khairudin (Semarak Ilmu Publishing, 2024)
The integration of immersive technology into educational settings has garnered substantial interest as a potential means to improve teaching and learning (TnL)experiences. The dynamic landscape of education demands innovative approaches to engage, motivate, and empower both educators and learners. Immersive technology, including Virtual Reality (VR), Augmented Reality (AR), as well as Mixed Reality (MR), provides uncommon probabilities to transcend traditional classroom boundaries and provide interactive and immersive learning experiences. However, to harness the full potential of immersive technology, a clear understanding of the conceptual frameworks guiding its implementation is essential. This study utilizes the PRISMA approach. Furthermore, the systematic search of academic databases using the Web of Science (WoS) as well as the Scopus database resulted in an extensive selection of studies, reviews and articles related to immersive learning. Following the implementation of an advanced search approach utilizing keywords (1. Immersive learning, 2. AR, as well as 3. Technology Impact on TnL), the systematic review process yielded a diverse array of articles. These articles were identified and included in the review due to their exploration of the conceptual frameworks that underlie the integration of immersive technology in the field of education. Additionally, the review reveals common themes and emerging trends within the field, shedding light on the diverse approaches to leveraging immersive technology for TnL. The final finding data is (n: 29), which reviews identified key themes. Expect validation to be divided into three themes, which are (1) Immersive learning, (2) AR, and (3) Technology Impact on TnL. Meanwhile, the findings emphasize the importance of well-defined theoretical foundations and best practices when implementing immersive technology for educational purposes. The review underscores the importance of ongoing research as well as innovation in the domain of immersive technology to fully exploit its potential for enhancing TnL experiences. In essence, this systematic review adds to the continued conversation about the efficient utilization of immersive technology in education and paves the way for further exploration and advancement in this field.